2019
DOI: 10.3390/ma12142249
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Thermal Cycling Resistance of AlxSi1−xN Coatings on Cu Substrates by Optimizing Al/Si Ratio

Abstract: The effect of the elemental composition of AlxSi1−xN coatings deposited on Cu substrates by magnetron sputtering on their structure, mechanical properties and thermal cycling performance is studied. The coatings with Al-Si-N solid solution, two-phase (AlxSi1−xN nanocrystallites embedded in the SixNy tissue phase) and amorphous structure were obtained by varying Al/Si ratio. It is shown that polycrystalline coatings with a low Si content (Al0.88Si0.12N) are characterized by the highest thermal cycling resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…TBCs, having lower thermal conductivity, are widely used in turbine blades, which are usually operated at very high temperatures [4,5,6,7]. Engines operating at high temperatures require materials with lower thermal conductivity in order to insulate the other parts of the engine from hot burning gases [8,9,10,11,12]. In addition to the Y 2 O 3 -ZrO 2 (YSZ) TBCs, it has been found that lanthanum-doping can effectively reduce the thermal conductivity of YSZ TBCs.…”
Section: Introductionmentioning
confidence: 99%
“…TBCs, having lower thermal conductivity, are widely used in turbine blades, which are usually operated at very high temperatures [4,5,6,7]. Engines operating at high temperatures require materials with lower thermal conductivity in order to insulate the other parts of the engine from hot burning gases [8,9,10,11,12]. In addition to the Y 2 O 3 -ZrO 2 (YSZ) TBCs, it has been found that lanthanum-doping can effectively reduce the thermal conductivity of YSZ TBCs.…”
Section: Introductionmentioning
confidence: 99%